(untitled) (Research, Society and Development, 2023)
Objective: This research aimed to analyze the epidemiological profile of reports of self-injured violence in the State of Piaui between 2017 and 2021. Methodology: This was a cross-sectional, observational, epidemiological study based on secondary data from the Notifiable Diseases Information System (SINAN), managed by the State Department of Health of Piaui (SESAPI). Data that are not related to self-harm were excluded. Furthermore, data from other databases did not participate in the study, only the Notifiable Diseases Information System (SINAN). Results: The results showed that pre-hospital care for self-inflicted injuries showed a great demand for female victims, young people and a higher density of occurrence in their homes. Between the years 2017 to 2021, self-inflicted injuries in the region of Piaui totaled 17,040 reported cases, with females having the highest incidence rates of notification totaling 71.1% and men totaling 28.9% of prevalence of injury cases self-provoked. The factors involved are diverse and among them the main ones are due to the use of alcoholic beverages, the most lethal means of self-injury and mortality were associated with the female gender. Conclusion: It is concluded that there was an increase in reports of self-inflicted injuries, with women, the elderly and young adults being the main victims. However, underreporting is still an obstacle for health surveillance and for better identification of suicidal behavior.